Urgent Care Proceedings for New-born Babies in England and Wales – Time for a Fundamental Review. (2nd March 2022) - Broadhurst, Karen; Mason, Claire; Ward, Harriet
Abstract: Emergency action to safeguard babies at birth who are at risk of significant harm is sanctioned in a number of international jurisdictions, including the UK, the USA, Canada, Australia, New Zealand, and Europe. However, there is widespread international disquiet about this practice, regarding breaches of parents' Articles 6 and 8 rights (Human Rights Act 1998), as well as the reliability of hasty decisions for children. This article reports the findings from the first large-scale qualitative study of professional and parental experience ( n = 307 participants) of compulsory State intervention at birth, with a specific focus on urgent care proceedings. Completed in eight local authority areas and corresponding health trusts in England and Wales (2019–2021), the study concludes that children's social care, hospitals, and the family courts are not yet sufficiently aligned around the needs of a small, but highly vulnerable population of mothers, their partners, and babies to ensure equitable, just or effective practice in cases of urgent care proceedings. Evidence is provided from both professionals and parents about the highly consequential nature of interim decisions, particularly where they result in physical separation of mother and baby at birth. The article advances knowledge about the distinctive challenges of issuing family court proceedings in the immediate post-partum period and calls for a fundamental review.